2004
DOI: 10.1246/cl.2004.982
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrochemical Fabrication of Metallic Nanopillar Array on Au Electrode Surface by the Template Technique

Abstract: This letter presents a novel, simple approach for direct electrochemical fabrication of metallic (Au or Pt) nanopillar array on gold electrode surface, employing cysteamine as a molecular anchor and anodic aluminum oxide as template without any sputtered metal as electrical conductor. The nanopillar arrays were grew directly on the electrode surface, and the prepared nanopillar array electrodes were used directly and easily to the electrochemical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Gold nanorods and nanowires play a central role in a wide variety of molecular applications from energy conversion to biological sensing and gene delivery . Considerable interest has been drawn into controllably synthesizing Au nanowires and understanding their size dependence on mechanical, electrical, photonic, and optical properties. Template-assisted electrodeposition into small pores is a technique commonly used to process Au nanowires and nanopillars on a large scale. The structure of electrodeposited Au nanowires has been investigated using transmission electron microscopy (TEM) and X-ray diffraction. TEM studies have revealed that 90% of Au nanowires fabricated by electrodeposition are fcc cylindrical crystals with [111] growth direction . In this letter, we use molecular dynamics simulation to describe a new type of size-dependent strengthening governed by interfacial plasticity in 〈111〉-oriented Au nanopillars consisting of growth twin boundaries.…”
mentioning
confidence: 99%
“…Gold nanorods and nanowires play a central role in a wide variety of molecular applications from energy conversion to biological sensing and gene delivery . Considerable interest has been drawn into controllably synthesizing Au nanowires and understanding their size dependence on mechanical, electrical, photonic, and optical properties. Template-assisted electrodeposition into small pores is a technique commonly used to process Au nanowires and nanopillars on a large scale. The structure of electrodeposited Au nanowires has been investigated using transmission electron microscopy (TEM) and X-ray diffraction. TEM studies have revealed that 90% of Au nanowires fabricated by electrodeposition are fcc cylindrical crystals with [111] growth direction . In this letter, we use molecular dynamics simulation to describe a new type of size-dependent strengthening governed by interfacial plasticity in 〈111〉-oriented Au nanopillars consisting of growth twin boundaries.…”
mentioning
confidence: 99%
“…Nanosphere lithography (NSL) [9][10][11][12] is a promising nanofabrication technology that is inexpensive, high-throughput, materials general a Author to whom correspondence should be addressed. and has been demonstrated to be well suited to fabricate nanoholes, [13][14][15] metallic nanomesh electrodes, 16,17 or silicon, [18][19][20] noble metal, 21 cobalt, 22,23 and gallium nitride nanorod arrays. 24 The function of NSL relies on templates for nanostructure patterning.…”
Section: Introductionmentioning
confidence: 99%
“…By incrementing the etch time, the diameter of the nanospheres is steadily reduced, resulting in samples with metallic nanoparticles of increasing size until they eventually merge to form hole arrays. 63 66 The NSL produced nanowells can be used as deposition template to fabricate silicon, 65 67 68 noble metal, 69 cobalt, 56 57 and gallium nitride nanorod arrays. 70 On the other hand, with the application of NSL and RIE, our previous work has demonstrated the fabrication of ordered arrays of in-plane, triangular cross-section nanowells with in-plane widths ranging from 44 to 404 nm and depths ranging from 25 to 250 nm.…”
Section: Introductionmentioning
confidence: 99%